Classification of regions according to the dominant innovation barriers: The characteristics and stability of regional archetypes in Germany - Tobias Johannes Hertrich; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2021)
Lagging regions differ in their characteristics, implying a need for tailor-made policy measures to improve the economic situation in these regions. However, while there are differences between these regions, certain "archetypes" of regions might exist that share the same obstacles to innovations, allowing for taking similar political measures. This paper analyses whether such archetypes can be identified in Germany, what characteristics they possess, and how stable they are. For this purpose, regional characteristics that are related to innovation barriers are identified and operationalized. Then, a cluster analysis is conducted for the German labor market area. Based on these characteristics six archetypes are identified. These archetypes are found to be relatively stable over time, confirming that such a classification can be considered a good basis for policy measures. Furthermore, this classification allows to identify trends that might lead to problems in the future and require policy attention.
Keywords: R11; R58; O38; 330; classification of regions; innovation barriers; cluster analysis; laggingregions